Ecocídio e os desafios da política externa contra a internacionalização da Amazônia - Vieira, Gabriely Vivian (2024)
The article addresses ecocide and the challenges of foreign policy against the internationalization of the Amazon. First, it demonstrates the challenges and how the foreign policy of the States where the Amazon is located can protect themselves from possible internationalization, guaranteeing their sovereignty but acting against ecocide. The article shows the contemporary aspects of the Amazon, the framing of ecocide in the New Latin American Constitutionalism and the intercontinental crisis surrounding the Forest in the context of the responsibilities of political managers. A mixed methodology is adopted, with qualitative and quantitative elements. It begins with the bibliographic research technique, with a literature review, to analyze the role of the ICC in holding political managers accountable with regard to ecocide in the Amazon, through books, scientific articles, legislation and international treaties. Next, a survey of quantitative data is presented through statistical analysis of secondary data, such as reports from government agencies, NGOs and international institutions. This assesses the incidence and severity of environmental crimes in the Amazon, as well as identifying patterns of mismanagement by political leaders. In addition, qualitative data (content analysis and cultural artifacts) are highlighted. The method used in the research is predominantly deductive, alternating in some sections with comparative and systematic methods. The corruption of political leaders has devastating consequences for the Amazon. Holding political leaders individually accountable by including ecocide as an independent crime in the Rome Statute provides a fair and independent trial by the ICC. The sovereignty of States is not violated, and effective accountability for the environmental damage caused is guaranteed. Therefore, it is essential that political leaders be held accountable for their ecocidal actions in the Amazon before the ICC, regardless of their position or sphere of activity.